2018
DOI: 10.3390/su10040928
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint and Driving Forces of Saline Agriculture in Coastally Reclaimed Areas of Eastern China: A Survey of Four Staple Crops

Abstract: Carbon emissions have always been a key issue in agricultural production. Due to the specific natural factors in the soil of saline agriculture, there are distinctive characteristics in saline agricultural production as compared with traditional agricultural zones. Here, we have adopted the theory of life cycle assessment and employed the Intergovernmental Panel on Climate Change (IPCC) greenhouse gas (GHG) field calculation to estimate the GHG emissions, derived from the staple crop productions (i.e., barley,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Additionally, the IPCC has a convenient data acquisition and simple calculation process, so it is applicable to the calculation of energy carbon footprint at all scales. Based on the current energy situation in Xi’an and the feasibility of the data, the carbon footprint of Xi’an could be calculated by referring to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories [ 20 , 21 , 22 ]. Through the analysis of the carbon footprints of the four accounts of energy consumption, industrial production, solid waste, and livestock, the total carbon footprint of Xi’an was summarized in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the IPCC has a convenient data acquisition and simple calculation process, so it is applicable to the calculation of energy carbon footprint at all scales. Based on the current energy situation in Xi’an and the feasibility of the data, the carbon footprint of Xi’an could be calculated by referring to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories [ 20 , 21 , 22 ]. Through the analysis of the carbon footprints of the four accounts of energy consumption, industrial production, solid waste, and livestock, the total carbon footprint of Xi’an was summarized in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the NPPs in natural vegetationcovered areas (grassland and forest) are generally similar to the observed NPP (Table 1). However, farmlands' NPP is significantly lower than that of the observed NPP; the main reason is the input of large amounts of fertilizers and pesticides during agricultural production for promoting crop yield (Li, Yang et al, 2018), which is not considered in the CASA model. By using remote sensing data and the CASA model, we can explore the spatiotemporal characteristics and trends of the NPP, which is beneficial to predict China's TEP.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Since then, the ecological footprint model has been extensively used as an essential research tool and analysis framework in sustainable development (Korkut, 2021;Ojonugwa et al, 2021;Umit, 2021;Zahid et al, 2021), socioeconomic development (Neagu, 2020;Enu and Sya, 2021), tourism development (Mehdi et al, 2012;Lin et al, 2017), and energy consumption (Sharma et al, 2021;Ullah et al, 2021). The application of the ecological footprint method in agriculture is divided into two parts: one is the impact of different agricultural production management methods on the agricultural environment, such as land use and farm management (Viglizzo et al, 2011, Hayo et al, 2007, and the second is to evaluate the sustainable utilization of agricultural resources such as water resources and arable land resources, combining the agricultural water footprint (Hoekstra et al, 2011;Wang et al, 2014), agricultural carbon footprint (Maier et al, 2017;Li et al, 2018), and crop footprint (Ferng, 2011;Budreski et al, 2016). In the ecological footprint study of China's agriculture, researchers, respectively, measured the ecological footprint and carrying capacity per capita of cultivated land, water area, grassland, and forest land in Henan (Cao, 2020), Guangxi (Zhang, 2020), and Shandong provinces (Yang et al, 2016), and all the studies found that the provinces have different degrees of ecological deficits.…”
Section: Introductionmentioning
confidence: 99%